Control of Phomopsis Blight of Egg Plant through Fertilizer and Fungicide Management - Hossain, MI; Islam, MR; Uddin, MN; Arifuzzaman, SM; Hasan, GN (International Journal of Agricultural Research, Innovation and Technology, 2013)
The experiments were conducted at Laboratory of the Department of Plant Pathology and in the farm of Sher-e-Bangla Agricultural University, Dhaka-1207, Bangladesh during Rabi season of the year 2007-2008. Four fungicides viz. Bavistin 50 WP (Carbendazim), Tilt 250 EC (Propiconazole), Cupravit 50 WP (Copperoxychloride) and Dithane M-45 (Mancozeb) and micronutrients (Gypsum, ZnO and Boric acid) were evaluated against Phomopsis vexans causing Phomopsis blight and fruit rot of eggplant. The fungicides and micronutrients either applied individually or in combination showed significant effect in terms of per cent leaf infection, fruit infection, leaf area diseased and fruit area diseased in comparison to control. Effect of each fungicide applied in combination with micronutrients always showed better performance in reducing disease incidence and disease severity than the fungicides applied alone. Among the fungicides, Bavistin 50 WP (0.1%) proved to be effective arresting the spore germination and mycelia growth of Phomopsis vexans assayed in in vitro test. Reduction of leaf area diseased caused by Bavistin 50 WP (0.1%) in combination with micronutrients were 58.17, 67.37, 78.41 and 85.25%, respectively at preflowering, post-flowering, fruiting and fruit ripening stages while Bavistin 50 WP (0.1%) alone reduced by 52.22, 58.67, 74.19 and 83.09%, respectively at those stages. Similarly reduction of fruit area diseased caused by Bavistin 50 WP (0.1%) in combination with micronutrients were 57.93 and 79.79%, respectively at fruiting and fruit ripening stages while Bavistin 50WP (0.1%) alone reduced by 56.93 and 76.14%, respectively at those stages. Micronutrients had little effect against the disease but significantly better than control. Int. J. Agril. Res. Innov. & Tech. 3 (1): 66-72, June, 2013 DOI: http://dx.doi.org/10.3329/ijarit.v3i1.16095